Graded particle zirconia ceramic and preparation method thereof

By using nanozirconia powder and porous microspheres as ceramic raw materials, combined with dry press forming and sintering processes, the existing ceramic toughening methods are solved, and the significant improvement of the fracture toughness of the ceramic is achieved.

CN119751056APending Publication Date: 2025-04-04HUNAN UNIV OF HUMANITIES SCI & TECH
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411815945.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing ceramic toughening methods are complex and have no significant toughening effect, making it difficult to effectively improve the fracture toughness of 3Y-TZP ceramics.

Method used

Nanozirconia powder and porous microspheres are used as raw materials for graded granular zirconia ceramics. The porous microspheres have a closed or connected microporous structure inside. The nanozirconia powder and porous microspheres are mixed in proportion and the ceramics are obtained by dry press molding and sintering.

Benefits of technology

By introducing microporous structures, the fracture toughness of the ceramic is significantly improved, the crack propagation path is extended, and it has a significant microcrack toughening effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751056A_ABST
    Figure CN119751056A_ABST
Patent Text Reader

Abstract

The invention discloses graded particle zirconia ceramic and a preparation method thereof.The graded particle zirconia ceramic comprises nano zirconia powder and porous microspheres, each porous microsphere is internally provided with a closed and / or communicated and through microporous structure, the particle size of each porous microsphere is 10-200 micrometers, and the particle size of each porous microsphere is 10-200 micrometers. And the aperture of the internal micropores is 0.3-1 [mu] m. According to the invention, the porous microsphere introduces a microporous structure into the graded particle ceramic, and the distribution of the microporous structure is consistent with that of the calcined microsphere in the graded particle ceramic, so that when the ceramic is damaged and the crack expands to a microporous area, the micropores at the tip of the crack bear larger stress due to a stress concentration effect; the microcrack toughening agent can induce main crack bifurcation or deflection, consumes crack propagation energy, prolongs a crack propagation path, and has an obvious microcrack toughening effect, so that the fracture toughness of the ceramic is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, in particular to a graded particle zirconia ceramic and a preparation method thereof. Background Art

[0002] 3 mol% yttrium-stabilized zirconia (3Y-TZP) ceramics have high strength and excellent fracture toughness. They are also non-toxic and biocompatible. They are widely used in structural ceramics, cutting tools, orthopedic implants, biomedicine and other fields.

[0003] Pure ZrO2 can present three crystal structures in different temperature ranges, namely monoclinic zirconia (m-ZrO2), tetragonal zirconia (t-ZrO2) and cubic zirconia (c-ZrO2). The above three crystal forms can be transformed into each other under certain conditions. Through the stabilization of the Y element, the tetragonal zirconia can exist at room temperature and transform to the monoclinic phase when subjected to external force, accompanied by a volume expansion of 3-5%, which can inhibit the expansion of cracks and play a role in phase transformation toughening. However, the magnitude of the induced stress of the phase transformation conversion is a function of the grain size and is affected by the type and concentration of the stabilizer. When the grain size exceeds the critical size, spontaneous transformation may also occur. Therefore, in order to give full play to the phase transformation toughening characteristics of zirconia ceramics, the zirconia grain size should be controlled to be lower than the critical size after sintering, so as to give full play to the phase transformation toughening characteristics of zirconia ceramics. For 3Y-TZP ceramics, the size is about 0.8μm. In addition, in ceramic materials, in general, the fracture toughness is proportional to the fracture strength and inversely proportional to the size of the internal defects. However, this is not entirely true for zirconia ceramics. When the size of the internal defects of zirconia is large, for example, greater than 30μm, the zirconia ceramics may fracture before the phase transformation toughening effect is activated, showing defect-controlled strength accompanied by low fracture toughness. When the defect size is less than 10μm, the strength and toughness of Y-PSZ are controlled by the strength of the phase transformation, and the fracture toughness K IC Can exceed 8MPa*m 1 / 2 ,Therefore, suppressing internal defects is also a key step in improving the fracture of zirconia ceramics.

[0004] 3Y-TZP ceramics have high strength, which can exceed 1GPa, but the fracture toughness is relatively low. The fracture toughness of zirconia ceramics with a grain size of 480nm is only 3.9MPa*m measured by the SEVNB method. 1 / 2There are many studies on ceramic toughening. Traditional ceramic toughening methods include particle dispersion toughening, phase transformation toughening, fiber / whisker toughening and synergistic toughening. The ceramics are toughened by mechanisms such as crack deflection and bridging through grain pullout, subgrain boundary pinning dislocations, transgranular fracture, and thermal residual stress fields caused by the mismatch of thermal expansion coefficients between the matrix and the second phase particles. In traditional toughening techniques, the bonding strength between the second phase and the ceramic matrix is ​​pointed out to be the key factor in ceramic toughening. The introduction of the toughened second phase improves the fracture toughness of zirconia ceramics to a certain extent. At the same time, the poor bonding between the second phase and the ceramic matrix may also increase the internal defects of the ceramics. When the defect size exceeds the critical size, it will deteriorate the fracture toughness of zirconia ceramics. The above ceramic toughening methods are relatively complex and the toughening effect is limited. Therefore, there are few reports on simple and easy-to-use toughened 3Y-TZP with significant effects. Summary of the invention

[0005] The invention provides a graded particle zirconia ceramic and a preparation method thereof, so as to solve the technical problems that the existing ceramic toughening method is complicated and the toughening effect is not significant.

[0006] According to one aspect of the present invention, a graded particle zirconia ceramic is provided, wherein the raw materials thereof include nano zirconia powder and porous microspheres.

[0007] The porous microspheres have closed and / or interconnected microporous structures inside, the particle size of the porous microspheres is 10-200 μm, and the pore size of the micropores inside the porous microspheres is 0.3-1 μm.

[0008] Furthermore, the porous microspheres account for 5-30%.

[0009] Furthermore, the porous microspheres account for 10-20%.

[0010] Furthermore, the method for preparing the porous microspheres comprises the following steps:

[0011] S1: dissolving 1-1.5 wt% of a dispersant in water, adding nano zirconium oxide powder, adjusting the pH of the solution with ammonia water, and ball milling to obtain a uniformly dispersed nano zirconium oxide powder slurry;

[0012] S2: adding a binder and continuing ball milling to obtain a spray granulation slurry of nano zirconium oxide powder;

[0013] S3: adding the spray granulation slurry into the spray granulation tower, spray granulation, collecting the first fraction of granulation powder, and obtaining porous granulation powder microspheres with a particle size of 10-200 um;

[0014] S4: placing the porous granulated powder microspheres in a muffle furnace and calcining them to obtain calcined porous microspheres.

[0015] Further, the dispersant is polyacrylic acid or polyacrylamide;

[0016] The amount of the dispersant used is 1-1.5wt% of the nano zirconium oxide powder.

[0017] Furthermore, the binder is one or more of polyvinyl alcohol, hydroxy cellulose and its derivatives, and polyacrylamide;

[0018] The amount of the binder is 0.5-1wt% of the nano zirconium oxide powder.

[0019] Furthermore, during the spray granulation in step S3, the inlet temperature is controlled to be 300° C., the outlet temperature is controlled to be 100° C., and the atomization frequency is controlled to be 20-35 Hz.

[0020] Furthermore, the calcination in step S4 is performed by raising the temperature to 1000-1600° C. at a rate of 1-20° C. / min and keeping the temperature for 0.5-6 h.

[0021] Furthermore, the method for preparing the nano zirconium oxide powder comprises the following steps:

[0022] Nano zirconium oxide powder is dispersed in an ethanol solution, and a grinding ball is configured to perform high-speed ball milling to obtain dispersed nano zirconium oxide powder; PVA solution is added to the dispersed nano zirconium oxide powder, stirred evenly, and then pressed into a hard block; the hard block is then crushed and ground into small particles to obtain compressed granulated powder of nano zirconium oxide; or

[0023] A dispersant is added to the nano zirconium oxide aqueous solution, and grinding balls are arranged. After high-speed ball milling, a PVA solution is added to continue the ball milling. The ball-milled slurry is directly spray-granulated to obtain the spray-granulated powder of nano zirconium oxide.

[0024] According to another aspect of the present invention, a method for preparing a graded zirconia ceramic particle is provided, using the raw material of the graded zirconia ceramic particle described above, comprising the following steps:

[0025] (1) adding nano zirconium oxide powder and porous microspheres in proportion to ethanol, stirring, drying, and further compressing and granulating to obtain zirconium oxide granulated powder with micro-nano particle size distribution; or adding zirconium oxide granulated powder and porous microspheres in proportion to a planetary ball mill and dry mixing to obtain zirconium oxide granulated powder with micro-nano particle size distribution;

[0026] (2) Dry-pressing the configured micro-nano particle-graded zirconium oxide granulated powder, followed by cold isostatic pressing, and finally sintering at normal pressure to obtain graded particle zirconium oxide ceramics.

[0027] The present invention has the following beneficial effects:

[0028] The present invention adopts nano zirconium oxide powder and porous microspheres as raw materials for graded particle zirconium oxide ceramics, wherein the porous calcined microspheres have closed or interconnected micropore structures inside, and most of the micropores have diameters of 0.3-1 μm. The porous microspheres in the graded particles introduce a micropore structure into the graded particle ceramics, and the distribution of the micropore structure is consistent with the distribution of the calcined microspheres inside the graded particle ceramics. When the ceramics are damaged and cracks extend to the micropore area, the micropores at the crack tips bear greater stress due to the stress concentration effect, which can induce the main crack to bifurcate or deflect, consume the energy of crack extension, extend the crack extension path, have a significant microcrack toughening effect, and thus improve the fracture toughness of the ceramics.

[0029] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention is further described in detail below. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0031] Figure 1 The figure is a process flow chart for preparing graded particle zirconia ceramics;

[0032] Figure 2 The morphology of porous microspheres after calcination;

[0033] Figure 3 The morphology of porous microspheres calcined at different temperatures;

[0034] Figure 4 This is a hardness test chart of graded particle zirconia ceramics;

[0035] Figure 5 This is an electron microscope image of the indentation of graded particle zirconia ceramics;

[0036] Figure 6 Schematic diagram of the evolution of the microporous structure in porous microspheres during the sintering process of graded particle ceramics;

[0037] Figure 7 Schematic diagram of the micropore toughening mechanism. DETAILED DESCRIPTION

[0038] The embodiments of the present invention are described in detail below with reference to the accompanying drawings. However, the present invention can be implemented in many different ways as defined and covered below.

[0039] The embodiment of the first aspect of the present invention provides a graded granular zirconia ceramic, whose constituent raw materials include nano-zirconia powder and porous microspheres, wherein the porous microspheres have a closed and / or interconnected microporous structure, the particle size of the porous microspheres is 10-200 μm, and the pore size of the micropores inside the porous microspheres is 0.3-1 μm.

[0040] The particle size of the porous microspheres can be any value in the range of 10-200 μm, that is, it can be any one or any combination of 10 μm, 20 μm, 40 μm, 50 μm, 80 μm, 100 μm, 120 μm, 150 μm, 180 μm, and 200 μm.

[0041] The pore size of the micropores inside the porous microspheres is 0.3-1 μm, that is, it can be any one or any combination of 300 nm, 400 nm, 500 nm, 800 nm, etc.

[0042] The present invention adopts nano zirconium oxide powder and porous microspheres as raw materials for graded particle zirconium oxide ceramics, wherein the nano zirconium oxide powder can be compressed granulated powder of nano zirconium oxide or spray granulated powder of nano zirconium oxide, and the porous calcined microspheres have closed or interconnected micropore structures inside, and most of the micropores have diameters of 0.3-1 μm. The porous calcined microspheres in the graded particles introduce a micropore structure into the graded particle ceramics, and the distribution of the micropore structure is consistent with the distribution of the calcined microspheres inside the graded particle ceramics.

[0043] The uniformly distributed porous calcined microspheres form a discontinuously distributed microporous area inside the ceramic. When the ceramic is damaged and the crack extends to the microporous area, the micropores at the crack tip bear a large stress due to the stress concentration effect, inducing the transformation of the zirconia matrix around the micropores from the tetragonal phase to the monoclinic phase, generating a large number of microcracks, and the microcracks are oriented along the force direction. The microcracks of adjacent micropores are connected together to form crack branches parallel to the main crack. If there are still a large number of micropores in the front section of the crack branch, the energy required for the crack branch to expand is less than the main crack, and the crack branch continues to expand and even turns into a main crack. If the direction of the microporous area is inconsistent with the crack extension direction, the crack will deflect along the microporous area with less energy consumption or the direction of dense micropores. Therefore, the micropores distributed in the ceramic crack tip area can induce the main crack to bifurcate or deflect, consume the energy of crack extension, extend the crack extension path, and have a significant microcrack toughening effect.

[0044] In an embodiment of the present invention, the porous microspheres account for 5-30%. The present invention adds porous microspheres to the nano zirconium oxide powder. As the content of the porous microspheres increases, the density of the ceramic decreases. Therefore, in order to make the ceramic have a good density and a high fracture toughness, the present invention sets the amount of the porous microspheres to 5-30%, that is, the amount of the porous microspheres can be any value or any range of values ​​among 5%, 8%, 10%, 12%, 14%, 18%, 20%, 23%, 25%, 28%, 30%, etc.

[0045] In a preferred embodiment, the porous microspheres account for 10-20%.

[0046] In an embodiment of the present invention, the method for preparing the porous microspheres comprises the following steps:

[0047] S1: dissolving 1-1.5 wt% (calculated based on the mass of the nano powder) of a dispersant in water, adding nano zirconium oxide powder, adjusting the pH of the solution with ammonia water, and ball milling to obtain a uniformly dispersed nano zirconium oxide powder slurry;

[0048] S2: adding a binder and continuing ball milling to obtain a spray granulation slurry of nano zirconium oxide powder;

[0049] S3: adding the spray granulation slurry into the spray granulation tower, spray granulation, collecting the first fraction of granulation powder, and obtaining porous granulation powder microspheres with a particle size of 10-200 um;

[0050] S4: The porous granulated powder microspheres are placed in a muffle furnace and calcined to obtain calcined porous microspheres. Figure 2 .

[0051] In the step S1, 1-1.5wt% (calculated based on the mass of the nano powder) of ammonium polyacrylate dispersant with a molecular weight of 5000000 is dissolved in water, the pH of the solution is adjusted to 10 by ammonia water, and ball milling is performed for 24 hours; in the step S2, 0.5-1wt% (calculated based on the mass of the nano powder) of a binder is added, and ball milling is continued for 24 hours to obtain a spray granulation slurry of nano powder.

[0052] Furthermore, the dispersant is polyacrylic acid or polyacrylamide; the amount of the dispersant is 1-1.5wt% of the nano zirconium oxide powder.

[0053] In an embodiment of the present invention, the binder is one or more of polyvinyl alcohol, hydroxy cellulose and its derivatives, and polyacrylamide;

[0054] The amount of the binder is 0.5-1wt% of the nano zirconium oxide powder.

[0055] In an embodiment of the present invention, during the spray granulation in step S3, the inlet temperature is controlled to be 300° C., the outlet temperature is controlled to be 100° C., and the atomization frequency is controlled to be 20-35 Hz.

[0056] In an embodiment of the present invention, in step S4, the zirconium oxide granulated powder is sieved, and the part between 250-350 mesh is taken, and the calcination is performed by heating to 1400-1600°C at a rate of 1-20°C / min, and keeping the temperature for 0.5-6h. Preferably, the temperature is raised to 1400-1600°C at a rate of 3°C / min, kept for 2h, and directly cooled to obtain the calcined porous microspheres.

[0057] The porous granulated powder microspheres obtained in step S3 have low crushing strength and will be crushed into nano primary particles during the dry pressing process. Calcining the granulated powder can increase its crushing strength, and the crushing strength of the granulated powder can be regulated by the calcining temperature, which is convenient for particle grading.

[0058] See also Figure 3 , Figure 3 The morphology of the prepared porous granulated powder microspheres and the granulated powder calcined at different temperatures is shown in Figure 2. Figure 3 (a) It can be seen that most of the porous granulated powder microspheres are spherical, a small amount is apple-shaped, and the particle size is between 30-80 μm. After calcination in step S4, the granulated powder becomes microspheres with a certain strength. Figure 3 (b), (c), (d) and (e) are the morphologies of calcined granulated powders at different temperatures. When the calcination temperature is 1000°C, most of the granulated powders are broken during transportation and cannot maintain their spherical structure; when the temperature is increased to 1200°C, a small amount of calcined microspheres are still broken and cannot meet the requirements of particle grading; when the temperature is further increased to 1400°C, the surface of the calcined microspheres obtained is dense and has high strength, and no broken granulated powder is found in the field of view; and when the temperature is further increased to 1600°C, the surface of the calcined microspheres is more dense, but it is also found that the large-sized microspheres and the small-sized microspheres have sintering necks and have coalesced, which increases the irregularity of the microsphere shape, which is not conducive to the flow of particles and filling the mold cavity. Therefore, the calcination temperature is preferably 1400-1600°C.

[0059] In an embodiment of the present invention, the method for preparing the nano zirconium oxide powder comprises the following steps:

[0060] Nano zirconium oxide powder is dispersed in an ethanol solution, and a grinding ball is configured to perform high-speed ball milling to obtain dispersed nano zirconium oxide powder; PVA solution is added to the dispersed nano zirconium oxide powder, stirred evenly, and then pressed into a hard block; the hard block is then crushed and ground into small particles to obtain compressed granulated powder of nano zirconium oxide; or

[0061] A dispersant is added to the nano zirconium oxide aqueous solution, and grinding balls are arranged. After high-speed ball milling, a PVA solution is added to continue the ball milling. The ball-milled slurry is directly spray-granulated to obtain the spray-granulated powder of nano zirconium oxide.

[0062] In the preparation process of the compressed granulated powder of the nano zirconium oxide, the nano zirconium oxide powder needs to be dispersed in an ethanol solution before use, and a zirconia grinding ball with a diameter of 6 mm is selected, and the grinding ball is configured according to 3 times the mass of the powder. The rotation speed is 400rmp / min, and the high-speed ball milling is performed for 6 hours to ensure that the agglomeration between the particles is opened. 10wt% of PVA is dispersed in deionized water and dissolved at high temperature to obtain a transparent PVA solution. A certain amount of nano zirconium oxide powder is weighed, and the PVA solution is added according to 0.5wt% of the powder, stirred evenly, and pressed into a hard block under a pressure of 50MPa. The hard block is broken and ground into small particles, and the powder passing through the 80-mesh screen is retained to obtain the compressed granulated powder of nano zirconium oxide.

[0063] The specific preparation process of the nano zirconium oxide spray granulation powder is as follows: prepare 65% zirconium oxide solution, add 0.5wt% d3019 dispersant (purchased from Dow Chemical), add 2wt% 10%wt PVA solution after ball milling at 400rmp / min for 24h, continue ball milling at 150rmp / min for 24h, directly spray granulate the ball-milled slurry, set the flow rate of the peristaltic pump to 20Hz, the atomization frequency of the spray granulator to 25Hz, the inlet temperature to 300°C, the outlet temperature to 100°C, and the material collected at the bottom of the tower is the nano zirconium oxide spray granulation powder.

[0064] According to another aspect of the present invention, a method for preparing a graded zirconia ceramic particle is provided, using the raw material of the graded zirconia ceramic particle described above, comprising the following steps:

[0065] (1) adding nano zirconium oxide powder and porous microspheres in proportion to ethanol, stirring, drying, and further compressing and granulating to obtain zirconium oxide granulated powder with micro-nano particle size distribution; or adding zirconium oxide granulated powder and porous microspheres in proportion to a planetary ball mill and dry mixing to obtain zirconium oxide granulated powder with micro-nano particle size distribution;

[0066] (2) Dry-pressing the configured micro-nano particle-graded zirconium oxide granulated powder, followed by cold isostatic pressing, and finally sintering at normal pressure to obtain graded particle zirconium oxide ceramics.

[0067] There are two methods for particle grading. One is to magnetically stir nano-zirconia powder and porous microspheres in ethanol according to a set ratio for 2 hours, dry, and further compress and granulate to obtain granulated powder of graded powder, denoted as MN. The other method is to directly dry-mix zirconia granulated powder and porous microspheres in a planetary ball mill according to a ratio for 6 hours to obtain mixed granulated powder particles, denoted as SZG. The granulated powder particles in the mixed granulated powder will be broken into nano-powder during the dry pressing process. The granulated powder is dry-pressed under a pressure of 80MPa, and the obtained green blank is further cold isostatically pressed at 200MPa, and the pressure is maintained for 1min. Finally, it is sintered at normal pressure to obtain graded zirconia ceramic particles. See the flow chart. Figure 1 .

[0068] The following examples describe the present disclosure in more detail, and these examples are intended for illustrative purposes only.

[0069] Example 1

[0070] The present embodiment provides a graded zirconia ceramic, whose constituent raw materials include nano-zirconia powder and porous microspheres, wherein the amount of the porous microspheres is 10%, and the porous microspheres have a closed and / or interconnected microporous structure inside, the particle size of the porous microspheres is 10-200 μm, and the pore size of the micropores inside the porous microspheres is 0.3-1 μm.

[0071] Example 2

[0072] The difference between this embodiment and embodiment 1 is that the amount of porous microspheres in embodiment 1 is 20%.

[0073] Example 3

[0074] The difference between this embodiment and embodiment 1 is that the amount of porous microspheres in embodiment 1 is 30%.

[0075] Comparative Example 1

[0076] This embodiment is basically the same as the embodiment 1, except that the raw materials for preparing the zirconia ceramic do not contain porous microspheres, specifically:

[0077] The nano-zirconia powder is compressed into granulated powder (without porous microspheres), molded at a pressure of 80 MPa, and then directly sintered to obtain zirconia ceramics, which are denoted as NZ.

[0078] The zirconia ceramics obtained by molding and sintering the spray granulated powder of nano-zirconia (not including porous microspheres) are denoted as ZG.

[0079] Experimental Case

[0080] The nano-zirconia powder was compressed into granulated powder and porous microspheres in ethanol according to a set ratio and magnetically stirred for 2 hours, dried, and further compressed and granulated to obtain granulated powder of graded powder. The granulated powder was dry-pressed at a pressure of 80 MPa, and the obtained green blank was further cold isostatically pressed at 200 MPa for 1 minute. Finally, the graded zirconia ceramics were sintered at normal pressure, which was recorded as MN. The ceramics with porous microsphere contents of 10% and 30% were recorded as MN-10 and MN-30, respectively.

[0081] Prepare 65% zirconium oxide solution, add 0.5% d3019 dispersant (purchased from Dow Chemical), add 2% 10% PVA solution after 400 rpm ball milling for 24 hours, continue ball milling for 24 hours at 150 rpm, spray granulate the milled slurry directly, set the flow rate of the peristaltic pump to 20 Hz, the atomization frequency of the spray granulator to 25 Hz, the inlet temperature to 300 ° C, the outlet temperature to 100 ° C, and the material collected at the bottom of the tower is the spray granulation powder of nano zirconium oxide. The spray granulation powder of nano zirconium oxide and porous microspheres are mixed according to the set ratio, and the zirconium oxide ceramics obtained by molding and sintering are recorded as ZGC; ceramics with porous microsphere contents of 5%, 10%, and 30% are recorded as ZGC-5, ZGC-10, and ZGC-30, respectively.

[0082] The sintered ceramics were cut into strips of 35*4*5mm, and the surfaces were polished with 300, 600, and 900 mesh diamond grinding discs in turn. The flexural test was carried out using an electronic universal testing machine. Ten specimens were prepared for each ceramic for testing and the data were recorded. The cut ceramic surfaces were polished and polished with 300, 600, 900, 1200, and 1500 mesh diamond grinding discs and alumina grinding fluid with a particle size of 3 and 1 μm in turn. The hardness of the polished specimens was tested using a Vickers hardness tester. Six specimens were prepared for each ceramic for testing and the data were recorded.

[0083] Figure 4 This is a hardness test chart of graded particle zirconia ceramics. After adding calcined microspheres, the hardness of graded particle ceramics is slightly reduced. The hardness of ceramics prepared by compression granulation is generally higher than that of ceramics prepared by spray granulation. Among them, NZ and MN-10 ceramics have the highest Vickers hardness, both 1295HV, and the data deviation is small. The hardness of ZG and ZG-5 samples is slightly lower, 1263HV and 1250HV respectively, but the data deviation is large. ZGC-10 and ZGC-30 ceramics have the lowest hardness, 1187HV and 1094HV respectively.

[0084] The fracture toughness of zirconia ceramics is measured by indentation method. The indentation is formed under 98N, and the length of the indentation crack extension is measured by SEM after 24 hours. ⅠC) is calculated by the formula. Where P is the maximum loading load, H and E are the hardness and Young's modulus of zirconia ceramics, and c is the average length of the diffusion cracks at the four corners of the indentation.

[0085]

[0086] Figure 5 The indentation electron microscope image of the graded particle zirconia ceramics is shown in Figure 1. The average length of the indentation crack c is measured, the value of the Young's modulus is taken as 210 GPa, and the hardness of the zirconia ceramics is substituted into the fracture toughness (K ⅠC )The fracture toughness of graded zirconia ceramics can be obtained through the formula.

[0087] It can be seen from the figure that the crack of the NZ ceramic obtained by the compression granulation method under the pressure of 98N is the longest, and the corresponding K IC 4.12MPa*m 1 / 2 , while the K of ZG ceramics prepared by spray granulation is IC 5.11MPa*m 1 / 2 When 10 wt% of porous calcined microspheres are added, the indentation crack extension of MN-10 ceramics prepared from compressed granulated powder is significantly shortened, and the corresponding K IC Reach 7.65MPa*m 1 / 2 , which is 85.68% higher than that of NZ ceramics and 49.70% higher than that of ZG ceramics prepared by the commonly used industrial preparation method. When 5wt% of porous calcined microspheres are added to the granulated powder, the extension crack of the indentation of ZGC-5 ceramic is shortened, and the corresponding K IC 6.33MPa*m 1 / 2 , which is 23.9% higher than that of ZG ceramics. When the content of calcined microspheres is further increased to 10wt%, the extended crack of ZGC-10 ceramic indentation is the shortest, and the corresponding KIC is 8.61MPa*m1 / 2, which is 68.49% higher than that of ZG ceramics.

[0088] Further analysis of the microstructure of graded particle ceramics revealed that the cross-section of MN-10 and MN-30 graded particle ceramics is distributed with aggregated closed or connected micropores, most of which have a diameter of 0.3-1 μm. The entire aggregated area is similar to the size of the calcined microspheres, such as Figure 6 As shown in the figure, the cross section of the calcined microspheres in the MN-10 compact after sintering at 1200°C is also full of micropores. It can be reasonably inferred that the calcined microspheres were not pressed before calcination, and the internal pores were preserved during the pressureless sintering process. Even after secondary sintering, the calcined microspheres could not achieve complete densification. Therefore, the calcined microspheres in the graded particles introduced a microporous structure into the graded particle ceramics, and the distribution of the microporous structure was consistent with the distribution of the calcined microspheres inside the graded particle ceramics.

[0089] It can be inferred that see Figure 7 , the uniformly distributed porous calcined microspheres form a discontinuously distributed microporous area inside the ceramic. When the ceramic is damaged and the crack extends to the microporous area, the micropores at the crack tip bear a large stress due to the stress concentration effect, inducing the transformation of the zirconia matrix around the micropores from the tetragonal phase to the monoclinic phase, generating a large number of microcracks, and the microcracks are oriented along the force direction. The microcracks of adjacent micropores are connected together to form crack branches parallel to the main crack. If there are still a large number of micropores in the front section of the crack branch, the energy required for the crack branch to expand is less than the main crack, and the crack branch continues to expand and even transforms into a main crack. If the direction of the microporous area is inconsistent with the crack extension direction, the crack will deflect along the microporous area with less energy consumption or the direction of dense micropores. Therefore, the micropores distributed in the crack tip area of ​​the ceramic can induce the main crack to bifurcate or deflect, consume the energy of crack extension, extend the crack extension path, and have a significant microcrack toughening effect. Therefore, the KIC of MN-10, ZGC-5, and ZGC-10 ceramics is significantly increased.

[0090] However, if the content of porous calcined microspheres in the ceramic is too high, the tightly packed calcined microspheres will form a continuously distributed microporous area inside the ceramic. In this case, when the ceramic cracks extend into the microporous area, the micropores also absorb energy to produce microcracks, but the main cracks will rapidly extend along the microcracks produced in the continuous microporous area under the action of stress, which is more likely to cause damage to the ceramic.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A graded particle zirconia ceramic, characterized in that: Its raw materials include nano zirconium oxide powder and porous microspheres. The porous microspheres have closed and / or interconnected microporous structures inside, the particle size of the porous microspheres is 10-200 μm, and the pore size of the micropores inside the porous microspheres is 0.3-1 μm.

2. The graded particle zirconia ceramic according to claim 1, characterized in that: The porous microspheres account for 5-30%.

3. The graded particle zirconia ceramic according to claim 2, characterized in that: The porous microspheres account for 10-20%.

4. The graded particle zirconia ceramic according to claim 1, characterized in that: The method for preparing the porous microspheres comprises the following steps: S1: dissolving 1-1.5 wt% of a dispersant in water, adding nano zirconium oxide powder, adjusting the pH of the solution with ammonia water, and ball milling to obtain a uniformly dispersed nano zirconium oxide powder slurry; S2: adding a binder and continuing ball milling to obtain a spray granulation slurry of nano zirconium oxide powder; S3: adding the spray granulation slurry into the spray granulation tower, spray granulation, collecting the first fraction of granulation powder, and obtaining porous granulation powder microspheres with a particle size of 10-200 um; S4: placing the porous granulated powder microspheres in a muffle furnace and calcining them to obtain calcined porous microspheres.

5. The graded particle zirconia ceramic according to claim 4, characterized in that: The dispersant is polyacrylic acid or polyacrylamide; The amount of the dispersant used is 1-1.5wt% of the nano zirconium oxide powder.

6. The graded particle zirconia ceramic according to claim 4, characterized in that: The binder is one or more of polyvinyl alcohol, hydroxy cellulose and its derivatives, and polyacrylamide; The amount of the binder is 0.5-1wt% of the nano zirconium oxide powder.

7. The graded particle zirconia ceramic according to claim 4, characterized in that: The atomization frequency during the spray granulation in step S3 is 20-35 Hz.

8. The graded particle zirconia ceramic according to claim 4, characterized in that: The calcination in step S4 is to raise the temperature to 1000-1600° C. at a rate of 1-20° C. / min and keep the temperature for 0.5-6 h.

9. The graded particle zirconia ceramic according to claim 1, characterized in that: The method for preparing the nano zirconium oxide powder comprises the following steps: Nano zirconium oxide powder is dispersed in an ethanol solution, and a grinding ball is configured, high-speed ball milling is performed, and drying is performed to obtain dispersed nano zirconium oxide powder; PVA solution is added to the dispersed nano zirconium oxide powder, stirred evenly, and then pressed into a hard block; then the hard block is crushed and ground into small particles to obtain compressed granulated powder of nano zirconium oxide; or A dispersant is added to the nano zirconium oxide aqueous solution, and grinding balls are arranged. After high-speed ball milling, a PVA solution is added to continue the ball milling. The ball-milled slurry is directly spray-granulated to obtain the spray-granulated powder of nano zirconium oxide.

10. A method for preparing graded particle zirconia ceramics, characterized in that: Using the raw material of the graded zirconia ceramic particles according to any one of claims 1 to 9, the method comprises the following steps: (1) adding nano zirconium oxide powder and porous microspheres to ethanol in proportion, stirring, drying, and further compressing and granulating to obtain zirconium oxide granulated powder with micro-nano particle size distribution; or adding zirconium oxide granulated powder and porous microspheres in proportion to a planetary ball mill and dry mixing to obtain zirconium oxide granulated powder with micro-nano particle size distribution; (2) Dry-pressing the configured micro-nano particle-graded zirconium oxide granulated powder, followed by cold isostatic pressing, and finally sintering at normal pressure to obtain graded particle zirconium oxide ceramics.

Citation Information

Cited By

  • Alumina / zirconia composite microsphere modified zirconia ceramic

    CN121717623A